Results of pedagogical experiments and their mathematical-statistical analysis - Sunnatullo Do'stov (Global Scientific Publishing, 2023)
This article describes in detail the results of pedagogical experiments and their mathematical and statistical analysis, the general principles of pedagogical research, the methodology of developing the program of pedagogical experiments, and the criteria for determining the effectiveness of pedagogical scientific research
Keywords: pedagogy; experimental work; mathematical-statistical analysis